2008
DOI: 10.1007/s10194-008-0044-8
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to Cinnarizine in refractory migraine prophylaxis: efficacy and tolerability. A comparison with sodium valproate

Abstract: The first author's given name and family name were transposed. His correct name is Mansoureh Togha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
2
5
0
1
Order By: Relevance
“…Patients' demographic information and characteristics of migraine episodes were not significantly different between the two groups. The proportion of patients who experienced one or more adverse events and the most common adverse events in both the groups were comparable with findings of most of the previous studies [10,11,14,15]. Somnolence was the most frequent side effect we have observed, in clinical setting this side effect could be reduced by the assumption of the entire dose of cinnarizine at the night sleep time.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Patients' demographic information and characteristics of migraine episodes were not significantly different between the two groups. The proportion of patients who experienced one or more adverse events and the most common adverse events in both the groups were comparable with findings of most of the previous studies [10,11,14,15]. Somnolence was the most frequent side effect we have observed, in clinical setting this side effect could be reduced by the assumption of the entire dose of cinnarizine at the night sleep time.…”
Section: Discussionsupporting
confidence: 92%
“…Amelin et al [14] reported a major reduction in migraine attacks frequency by studying vertigolytic effect of cinnarizine in a group of patients with migraine. Togha et al [10,15] in an open-label, double-blind, parallel-group clinical trial reported significant improvement in migraine headache frequency, duration and intensity after administration of 25-mg cinnarizine every 8 hours; however, there were some significant side effects including dry mouth, fatigue, somnolence, nausea, constipation and hypotension [8]. Togha et al [15] in a clinical trial compared the effect of cinnarizine versus valproate in refractory migraine prophylaxis and showed that cinnarizine is an effective and safe prophylactic agent even in severe cases of migraine headache.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Широко применяются в клинической практике с превентивной целью и блокаторы кальциевых каналов (флунаризин, циннаризин). В исследованиях при сравнении циннаризина с бета-блокатором (пропрано-лол) и антиконвульсантом (вальпроат) циннаризин про-демонстрировал сходную профилактическую эффектив-ность и переносимость [46,47].…”
Section: применение фезама при мигрениunclassified